Decision Analysis as an Aid to Strategy - Thomas, Howard (Institutional Knowledge at Singapore Management University, 1984)
Statistical decision theory is a theory of decision-making, i.e., of selecting among alternatives. It is not a theory of problem solving, i.e., of finding the cause of a particular set of symptoms. Thus, if the problem or opportunity is defined poorly even the best analysis thereafter will be of limited value. In fact, it could be detrimental.